2020
DOI: 10.2337/dc20-1815
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c Change and Diabetic Retinopathy During GLP-1 Receptor Agonist Cardiovascular Outcome Trials: A Meta-analysis and Meta-regression

Abstract: BACKGROUNDLong-term glycemic control reduces retinopathy risk, but transient worsening can occur with glucose control intensification. Glucagon-like peptide 1 receptor agonists (GLP-1RA) lower glucose, but the long-term impact on retinopathy is unknown. GLP-1RA cardiovascular outcome trials (CVOTs) provide long-term follow-up, allowing examination of retinopathy outcomes. PURPOSETo examine the associations between retinopathy, HbA 1c , systolic blood pressure (SBP), and weight in GLP-1RA CVOTs. DATA SOURCESSys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 31 publications
4
44
0
2
Order By: Relevance
“…Sub‐analysis has found that this increased risk is driven by rapid reduction in HbA1c in insulin‐treated patients with diabetic retinopathy, long‐standing disease and high HbA1c levels at baseline 55 . While the CVOTs (details below) were not powered or designed to assess retinopathy outcomes, a meta‐analysis of the CVOTs found that the degree of HbA1c reduction was correlated with the risk of retinopathy progression 56 . The upcoming FOCUS trial will clarify a potential link as well as establish the role of sc.…”
Section: Clinical Considerations When Prescribing Glp‐1rasmentioning
confidence: 99%
“…Sub‐analysis has found that this increased risk is driven by rapid reduction in HbA1c in insulin‐treated patients with diabetic retinopathy, long‐standing disease and high HbA1c levels at baseline 55 . While the CVOTs (details below) were not powered or designed to assess retinopathy outcomes, a meta‐analysis of the CVOTs found that the degree of HbA1c reduction was correlated with the risk of retinopathy progression 56 . The upcoming FOCUS trial will clarify a potential link as well as establish the role of sc.…”
Section: Clinical Considerations When Prescribing Glp‐1rasmentioning
confidence: 99%
“…Sterling et al (2021) linked the exposure to GLP-1R agonists ( i.e., dulaglutide, liraglutide, lixisenatide, exenatide , and semaglutide ) to a low risk of developing open-angle glaucoma ( Sterling et al, 2021 ). However, previous studies have raised concern that treatment with GLP-1R agonists may increase the risk of diabetic retinopathy, making them less favorable to be used against diabetic eye complications ( Diabetes Control and Complications Trial Research Group, Nathan et al, 1993 ; No authors listed, 1998 , 1999 ; Aiello and Dcct/Edic Research Group, 2014 ; Green et al, 2015 ; Marso et al, 2016b ; Jingi et al, 2017 ; Tang et al, 2018 ; Bain et al, 2019 ; Lim et al, 2019 ; Bethel et al, 2021 ). Nevertheless, this effect of GLP-1R agonists is most likely caused by a rapid decrease in patients’ blood glucose levels as discussed later ( Vilsbøll et al, 2018 ; Bain et al, 2019 ; Lim et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, including the DCCT, SUSTAIN-6, LEADER and TECOS trials, have linked exposure to incretin-based therapies and other hypoglycemic agents (i.e., insulin , injectable semaglutide, liraglutide , and oral sitagliptin ) to the exacerbation of pre-existing retinopathy ( Diabetes Control and Complications Trial Research Group, Nathan et al, 1993 ; No authors listed, 1998 , 1999 ; Aiello and Dcct/Edic Research Group, 2014 ; Green et al, 2015 ; Marso et al, 2016a , b ; Jingi et al, 2017 ; Tang et al, 2018 ; Bain et al, 2019 ; Lim et al, 2019 ; Bethel et al, 2021 ). For example, the SUSTAIN-6 trial showed that the risk of retinopathy events was increased during the first 2 months of treatment with injectable semaglutide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first month of the trial, most events coincided with a rapid and massive drop in HbA1c in dysregulated patients with pre-existing retinopathy. A recent CVOT meta-analysis showed that the magnitude of HbA1c reduction was correlated with retinopathy risk and was not associated with GLP-1RA treatment per se ( 50 ). However, a direct and unknown action of GLP-1RAs cannot be excluded.…”
Section: Effects Of Glp-1ras In Type 2 Diabetesmentioning
confidence: 99%